2022
DOI: 10.1038/s41419-022-04859-w
|View full text |Cite
|
Sign up to set email alerts
|

m6A methylation mediates LHPP acetylation as a tumour aerobic glycolysis suppressor to improve the prognosis of gastric cancer

Abstract: LHPP, a histidine phosphatase, has been implicated in tumour progression. However, its role, underlying mechanisms, and prognostic significance in human gastric cancer (GC) are elusive. Here, we obtained GC tissues and corresponding normal tissues from 48 patients and identified LHPP as a downregulated gene via RNA-seq. qRT-PCR and western blotting were applied to examine LHPP levels in normal and GC tissues. The prognostic value of LHPP was elucidated using tissue microarray and IHC analyses in two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…On the contrary, silencing of LHPP induced converse results. Consist with Lin et al 12 our further experiments revealed that LHPP was critically involved in the regulation of the migration and invasion of GC cells. In the light of these findings, we concluded that LHPP might inhibit the migration, invasion abilities and EMT process of GC cells.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the contrary, silencing of LHPP induced converse results. Consist with Lin et al 12 our further experiments revealed that LHPP was critically involved in the regulation of the migration and invasion of GC cells. In the light of these findings, we concluded that LHPP might inhibit the migration, invasion abilities and EMT process of GC cells.…”
Section: Discussionsupporting
confidence: 54%
“…Until recently, researchers found LHPP function as a tumor suppressor gene in multiple cancers. Nevertheless, only one article concerns the relationship between LHPP and GC progression for now 12 . From our perspective, LHPP may exert its anti-tumor effects through multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional experiments have shown that WTAP bound to the 3′‐UTR m 6 A site of HK2 enhances the glycolytic capacity of GC cells 376 . Additionally, METTL14 increases the mRNA stability of the acetylated protein LHPP, thereby attenuating glycogen synthase kinase‐3β (GSK‐3β) phosphorylation and the Wnt signaling pathway to suppress aerobic glycolysis in GC cells 377 . In PDAC, YTHDC1 augments miR‐30d expression to attenuate aerobic glycolysis by suppressing the activity of the transcription factor RUNX1 along with the promoters of SLC2A1 and HK1 378 .…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“…METTL14 deficiency in renal cell carcinoma (RCC) promotes distal lung metastasis by enhancing glycolytic reprogramming [ 95 ]. However, a glycolysis-promoting role of METTL14 through the repression of LHPP, which inhibits cancer cell metabolism, has been reported in gastric cancer (GC) [ 96 ]. Other m 6 A methyltransferases, including WTAP and KIAA1429, have been found to have a glycolysis-promoting role in cancers [ 97 99 ].…”
Section: A Methylation Regulates Time Reprogramming and Affects Immun...mentioning
confidence: 99%